Dampak Bantuan Usaha Islamic Relief Bagi UMKM Masyarakat Huntap Duyu - Ardiansyah Ardiansyah; Elimawaty Rombe; Syamsul Bachri; Pricylia Chintya Dewi (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to find out the impact of the Islamic Relief business assistance program for MSMEs in the Duyu community. Islamic Relief business assistance program for MSMEs specifically for the Duyu Huntap Community affected by the disaster. The research approach is qualitative research through the CIPP model evaluation method (context, input, process, product). Data was collected by conducting observations and based on program data search results starting from the beginning of the Islamic Relief Thematic KKN on September 11, 2023 to January 5, 2024. Data analysis techniques consist of data reduction, data presentation and conclusion drawing. The results of this study indicate that each aspect of CIPP has been implemented according to the procedure. The business assistance program for MSMEs in Duyu shelter is a form of post-disaster economic defense. This means that the development of the Islamic Relief business assistance program for MSMEs in the Duyu Huntap Community has been successful and has an impact on business actors in maintaining and starting a business. The context aspect shows that all forms of preparation in providing this program are carried out carefully so that they can have an impact on the success of the business assistance program for MSMEs in Duyu. The input aspect is designed according to the correct official legal umbrella. The process aspect is carried out starting from socialization activities to the distribution of business assistance for MSMEs to the Duyu Huntap community procedurally to have an impact on success targeting business actors who need business capital assistance. In the product aspect, it is known that the business assistance program for MSMEs has a good impact on the economic recovery of business actors in Huntap Duyu.